Climate-Smart Villages: a community approach to sustainable agricultural development - Aggarwal, Pramod K.; Zougmoré, Robert B.; Kinyangi, James (2013)
The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) is working with communities to develop ‘Climate-Smart Villages’. These are sites where researchers, local partners, and farmers collaborate to evaluate and maximize synergies across a portfolio of climate-smart agricultural interventions. We aim to improve farmers’ income and resilience to climatic risks and boost their ability to adapt to climate change.